Prevalence of Hypovitaminosis D in Pregnancy and Potential Benefits of Oral Supplementation - Saccone, Gabriele; Buonomo, Giorgia; Guerra, Serena; Gentile, Doriana; Di Spiezio Sardo, Attilio (American Journal of Perinatology, 2025)
This study aimed to evaluate prevalence of hypovitaminosis D in a cohort of Italian pregnant women, and to evaluate potential benefits of oral supplementationObservational cohort of women with singleton gestations who were referred to our institution for first trimester prenatal visit. Screening for hypovitaminosis D was performed at the time of first trimester routine scan between 11 and 13 weeks of gestations. Women were offered measurement of serum 25-hydroxyvitamin D (25[OH]D). Levels of 25(OH)D are interpreted as follows: 12 to <20 ng/mL: Vitamin D insufficiency; < 12 ng/mL: Vitamin D deficiency. Women with Vitamin D insufficiency or deficiency were offered daily oral supplementation at the dose of 2.000 UI, along with folic acid. The primary outcome was the prevalence of hypovitaminosis D in our cohort.During the study period, between January 2023 and January 2024, 250 pregnant women were included in the study and screened for 25(OH)D. More than half of the screened women had 25(OH)D < 20 ng/mL, with a prevalence of <12 ng/mL of 14%. Out of the 140 (140/250 = 56%) women with 25(OH)D < 20 ng/mL, 127/140 (90%) accepted supplementation with Vitamin D, whereas 13 refused the therapy for fear of teratogenic effects of the fetus. The overall rate of preterm delivery before 37 weeks was 8.4%, whereas the incidence of preeclampsia was 2.8%. Rate of preterm delivery was higher in women who did not received supplementation (9.5 vs. 30.8%), but the study was not powered for such comparison.Hypovitaminosis D has high prevalence in pregnant women. Universal screening in the first trimester with measurement of serum 25-hydroxyvitamin D (25[OH]D) can identify women at risk that may benefit of oral supplementation.
Keywords: folic acid; hypertension; prevention; recurrent; supplementation